7-(x/8)=(x/6)

Simple and best practice solution for 7-(x/8)=(x/6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(x/8)=(x/6) equation:


x in (-oo:+oo)

7-(x/8) = x/6 // - x/6

7-(x/8)-(x/6) = 0

7-7/24*x = 0 // - 7

-7/24*x = -7 // : -7/24

x = -7/(-7/24)

x = 24

x = 24

See similar equations:

| 4u^2-11u+6= | | (3c-4)= | | 3x+7=-32 | | 3x^2-2x-21= | | (7y-2)/3=-4/(y-3) | | 10/2p-6/20=15/20p+9/20 | | Ax-1=bx | | 18-4200/x^2 | | (3x^2+2x-9)-(6x^2-8)= | | 25200/24 | | 7-2800/x^2=0 | | 8/32= | | log(9)7+log(9)4= | | 5x-9=x+6 | | x^2+7x-6=9x-6 | | (3x^7-3x^4+8x)+(6x^7-5x^4+7x)= | | 10=5/2v | | 5=8/x+2 | | x^2-2x-7=1 | | X+20x-8=0 | | 2w/7=6 | | X/3-1=x/4 | | 3/2y=30 | | 12/5=4z | | 3(x-2)-1=-2(4-6x)+3 | | 0=2x^2+5x | | 2a-18.2=a+2.8 | | -x-1=-5 | | 10u+6=3u+48 | | y^2+x^2=r^2 | | x^3+2x^2-29x+42=0 | | oz=tbsp |

Equations solver categories